Znaczenie uczestnictwa w grupach wsparcia w powrocie do równowagi psychicznej osób po doświadczeniu straty dziecka = Significance of participation in support groups in psychological recovery after experiencing the loss of a child - Trepka-Starosta, Justyna; Starosta, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper discusses issues related to grief after the death of the child, participation insupport groups and its role in the process of coping with loss. The aim is to present how participationin support groups affects the difficult process of mourning. The theoretical basics in this studywere: conceptiont of grief process by Sanders (2001) and social support by Sęk and Cieślak (2011).To verify the hypothesis the quantitative research was conducted on a group of 66 parents betweenthe ages of 27 to 63 years old.
Keywords: strata; żałoba; wsparcie; grupa wsparcia; radzenie sobie ze stratą; sens życia; death of the child; mourning; coping with loss; support group; social group